2017
DOI: 10.29063/ajrh2017/v21i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Partner Support for Family Planning and Modern Contraceptive Use in Luanda, Angola

Abstract: Husband's/partner's support for family planning may influence a women's modern contraceptive use. Socio-demographic factors, couple communication about family planning, and fertility preferences are known to play a role in contraceptive use. We conducted logistic regression analysis to investigate the relationship between perceived husband's/partner's approval and husband's/partner's encouragement of modern contraceptive use, adjusting for socio-demographic factors and recent couple communication about family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 35 publications
7
51
2
5
Order By: Relevance
“…Wives' encouragement is key to motivating their husbands' participation in the adoption of contraceptives. 40,41 This study also shows that the use of modern contraceptive methods by couples increases the probability of inter-spousal communication. Family planning communication between husbands and wives is strongly associat ed with deflating anti-contraceptive rumors.…”
Section: Discussionmentioning
confidence: 57%
“…Wives' encouragement is key to motivating their husbands' participation in the adoption of contraceptives. 40,41 This study also shows that the use of modern contraceptive methods by couples increases the probability of inter-spousal communication. Family planning communication between husbands and wives is strongly associat ed with deflating anti-contraceptive rumors.…”
Section: Discussionmentioning
confidence: 57%
“…Other studies also have found that female empowerment expands women’s choices and ability to make decisions, including reproductive health decisions, and it also leads to improved health-seeking behavior such as modern contraceptive use [ 14 ]. Although many studies have investigated the role of women’s empowerment in the decision-making process [ 49 ], they assessed other aspects of the decision-making such as the decision to seek health care, household decisions, financial decisions in addition to reproductive decision [ 50 52 ]. Our analysis found a positive association between community-level contraceptive decision and modern contraceptive use; however, we did not have the means to further investigate the women’s empowerment more deeply.…”
Section: Discussionmentioning
confidence: 99%
“…Upaya pengendalian laju pertumbuhan penduduk Indonesia dicanangkan pemerintah melalui program Keluarga Berencana (BKKBN, 2015). Dukungan suami dinilai cukup berkontributif dalam keputusan penggunaan metode kontrasepsi (Prata, et al, 2017), mengingat pengambilan keputusan dalam mayoritas keluarga di Indonesia adalah suami (Putri & Lestari, 2015). Suami yang memahami tentang pentingnya dan mendukung perencanaan keluarga yang baik akan memungkinkan peluang kepesertaan dalam KB (Ezeanolue, et al, 2015…”
Section: Pendahuluanunclassified
“…Sebagaimana hasil penelitan terdahulu yang menunjukkan bahwa pemilihan metode kontrasepsi dalam rumah tangga melibatkan musyawarah antara suami dengan istri untuk mendapatkan keputusan atau kesepakatan bersama (Dasri, 2016). Hal ini juga telah disampaikan dalam penelitian terdahulu yang menunjukkan bahwa penggunaan kontrasepsi ditentukan oleh proses dan hasil komunikasi antar pasangan (Prata, et al, 2017).…”
Section: Pembahasanunclassified